Perfil da resistência aos fármacos antituberculose em pacientes atendidos nos serviços de saúde no estado do Piauí - Gonçalves, Walterlene de Carvalho (2012)
Tuberculosis is an infectious and contagious disease which persists throughout world history as a serious public health problem. It is caused by the complex Mycobacterium tuberculosis. The Ministry of Health considers tuberculosis a priority disease in Brazil, because the country occupies the 17th place among 22 developing countries, all together responsible for 80% of the worldwide cases of this disease. There has been an increase in the number of bacterial resistance cases to antituberculosis drugs. This study was descriptive and retrospective study of the years 2005 to 2007 and prospective from 2008 to 2009, aiming to assess the diagnosis of tuberculosis and the profile of antituberculosis drug resistance tests in 563 patients treated in the Health Services of the State in LACEN -PI, through culture and sensitivity testing of various biological specimens. From 563 cases, 123 were positive to culture, of which about 91.8% had the pulmonary form of the disease, being 65% of the population in focus consisting of male sex individuals. The mean age in years was 43.97 ± 16.81 (1 - 89). In all years, the cases treated exceeded in 92.6% the new cases. No resistance was identified in 68 cases (55.3%). The rate of primary and acquired resistance was 3% and 97% respectively. It was found 39 cases (31.7%) of multi-drug resistance, 15 cases (12.1%) of single drug resistance, and 14 cases (11.3%) of full range drug resistance. The conclusion is that levels of resistance found are high. Thus, it is necessary to monitor the resistance levels, in addition to adequate control of tuberculosis cases in Piauí, by expanding the culture testing and sensitivity testing for early diagnosis. It should also be encouraged to develop more research to standardize new diagnostic tests that are practical, fast, easily run, low cost and possessing high specificity and sensitivity for the disease